2000
DOI: 10.1002/(sici)1097-4652(200005)183:2<145::aid-jcp1>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation and cancer

Abstract: The methylation of DNA is an epigenetic modification that can play an important role in the control of gene expression in mammalian cells. The enzyme involved in this process is DNA methyltransferase, which catalyzes the transfer of a methyl group from S-adenosyl-methionine to cytosine residues to form 5-methylcytosine, a modified base that is found mostly at CpG sites in the genome. The presence of methylated CpG islands in the promoter region of genes can suppress their expression. This process may be due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
218
1
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(227 citation statements)
references
References 101 publications
4
218
1
4
Order By: Relevance
“…These observations might result from the fact that cancer cells often present aberrant methylation, their genome being generally hypomethylated and locally hypermethylated, notably in CpG islands (Baylin et al, 1998;Momparler and Bovenzi, 2000;Robertson and Jones, 2000). Our study suggests that the main methylation abnormalities at the GPC3 promoter level seems to be losses of methylation in NBs and the opposite in WTs.…”
Section: Discussionmentioning
confidence: 65%
“…These observations might result from the fact that cancer cells often present aberrant methylation, their genome being generally hypomethylated and locally hypermethylated, notably in CpG islands (Baylin et al, 1998;Momparler and Bovenzi, 2000;Robertson and Jones, 2000). Our study suggests that the main methylation abnormalities at the GPC3 promoter level seems to be losses of methylation in NBs and the opposite in WTs.…”
Section: Discussionmentioning
confidence: 65%
“…Previous study indicated aberrant methylation of DNA plays an important role in epigenetic changes and occurrence of various cancers (Momparler and Bovenzi, 2000). Lack of global DNA methylation may cause the instability of gene, and thus promote the process of cancer development (Sato and Meltzer, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established in cancer and stem cells that high CpG methylation occurs at the promoter region correlates with inhibition of gene expression (Momparler and Bovenzi, 2000;Miranda and Jones, 2007;Altun et al, 2010). Moreover, there are several studies that highlight the importance of DNA methylation in disease and during normal development of organisms (Martin et al, 1999;Mhanni and McGowan, 2004;Linhart et al, 2007;Ehrlich et al, 2008).…”
Section: Dna Methylationmentioning
confidence: 99%